2022
DOI: 10.3390/su142315972
|View full text |Cite
|
Sign up to set email alerts
|

Automotive Electrification Challenges Shown by Real-World Driving Data and Lifecycle Assessment

Abstract: Electric mobility is considered a solution to reduce carbon emissions. We expanded a lifecycle assessment with data on technical limitations and driving habits (based on real-world data) in order to identify the environmentally optimal drivetrain for each individual driving behavior with current and projected technologies, focusing on CO2 emissions. By combining all data, an environmentally optimal European drivetrain mix is calculated, which is dominated by fuel-cell electric vehicles (50% in 2020, 47% in 203… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The use of electric vehicles has been positively received by the market, consumers and governments, making them increasingly popular in European societies (Zagorskas & Burinskiene, 2020). The literature also contains articles on the design of energy-efficient powertrains involving optimisation of components, systems and controls (Ehsani et al, 2021;Neidhardt et al, 2022).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The use of electric vehicles has been positively received by the market, consumers and governments, making them increasingly popular in European societies (Zagorskas & Burinskiene, 2020). The literature also contains articles on the design of energy-efficient powertrains involving optimisation of components, systems and controls (Ehsani et al, 2021;Neidhardt et al, 2022).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…In support of these principles, customized tools can be found in literature that assess the sustainability of solutions selected by the designer [6]. More specifical ly, the attention to green solutions is heavily focused on vehicle electrification [7]. Numerous articles can be found that highlight the sustainability of electric vehicles compared to internal combustion cars.…”
Section: Introductionmentioning
confidence: 99%